Keterampilan Guru Dalam Pengelolaan Ruang Kelas Mata Pelajaran SKI di Mi Miftaahul Hudaa Depok - Nafisatun Nadhifah; Siskha Putri Sayekti; Akbar Fahlevi (Jurnal Seumubeuet, 2023)
This study aims to describe the performance of teacher skills in managing classrooms at MI Miftaahul Hudaa Depok. Class V MI teachers are able to manage classes well with limited school facilities. The teacher is able to manage classes with limited teacher skills. The teacher is able to manage classes. with skills the teacher is able to make the class active, and students can easily understand the SKI learning explained by the grade V teacher. These skills should be mastered by the teacher, especially for elementary school teachers in dealing with children's behavior that is truly unique. This study uses a qualitative research method to describe teacher skills in managing classrooms with limited facilities, which aims to find out teachers in managing SKI learning classrooms at MI Miftaahul Hudaa Depok. making SKI learning which is usually boring become more interesting, Improving their professional skills in managing the learning process in class. *After conducting research, it was found that the teacher's skills in classroom management based on the teacher's position as educational designer are controlling the classroom, seating, arranging learning places, and arranging class beauty. On the other hand, the position as an organizer is a teacher forming an organizational structure, compiling picket notes, and forming student study groups. There is also for the position of being a motivator, the teacher provides motivation in the form of applause, praise, intermezzo, and ice breaking to students. Create a supervisor position where the learning outcomes of the students will not be good either. Thus it can be concluded that classroom management is one of the determining variables on learning outcomes.